Effectiveness of Different Packaging Materials on Storage Ability of Lime (Citrus aurantiifolia Swingle) - Reddy, P. Manoj; Kumar, Alok; Piloo, Ng.; Joykumar, Ng.; Singh, N. Gopimohon; Sharma, Malay Marut (International Journal of Economic Plants, 2024)
The present study was undertaken at the Department of Horticulture, College of Agriculture, Iroisemba, Central Agricultural University, Imphal during 2021–2022 with the objectives to study the effectiveness of different packaging materials on shelf life of lime and their impact on quality of fruit during storage. Acid lime is one of the important commercial cultivar in India. The genus is significant economically because many of its species are grown for their fruit, which is consumed raw or pressed to extract juice that is then preserved to make pickles and marmalades. Experimental design was followed in Randomised Block Design (RBD) constituting eight treatments combinations as follows: T1: Low density polyethylene (LDPE) bags without ventilation, T2: Low density polyethylene (LDPE) bags with 1% ventilation, T3: Low density polyethylene (LDPE) bags with 3% ventilation, T4: Low density polyethylene (LDPE) bags with 5% ventilation, T5: Tray overwrapping with cling film, T6: Vacuum packging, T7: Plastic punnet, T8: No Packaging (control). Physiological loss in weight (%), decay percentage (%), specific gravity (g cm-3), TSS (ºBrix), titrable acidity (%), TSS acid ratio, ascorbic acid (mg 100 ml-1) and sensory quality of the fruits were recorded at fixed interval of time period. From the obtained result, it can be concluded that vacuum packaging was found to be best treatment for extending shelf life of lime up to 36–38 days maintaining a low physiological loss in weight, good sensory, minimum spoilage and other physio-chemical characters at the same time under ambient condition of storage.